One hundred years since the "Bolshevik Triennium" (1918-1920): agrarian unionism and collective actions during the Restoration crisis - Sánchez Castillo, Adrián (Hispania Nova, 2020)
Agrarian conflicts that erupted from 1918 to 1920 in rural Spain, with an epicentre in Andalusia and namely in the province of Cordoba, went down in history as the "Bolshevik Triennium". This term, coined by Juan Díaz del Moral in his classic Historia de las agitaciones campesinas andaluzas (1929) encompasses a strike offensive led by thousands of day labourers, tenants and small landowners unparalleled in the contemporary history of Spain. This work aims to analyse that conflict as a collective action phenomenon, framing it in the national and international political context, identifying its time, regional and sectoral discontinuity, as well as contributing to the updating of historiography on that topic as we celebrate one hundred years since those events took place.